Group Processes in the Classroom, Second Edition - Schmuck, Richard A.; Schmuck, Patricia A. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
How the processes of group interaction combine to help or hinder cognitive and affective learning in the classroom is discussed. Numerous concepts about interaction in the classroom along with the available research on those concepts expressed in practical terms are presented. Implications for teachers are emphasized. The book is designed to be used by preservice teachers in their curriculum, instruction, or educational psychology courses and by experienced teachers in in-service training sessions. Chapter one lays the groundwork for the rest of the book by offering a social psychological perspective on classroom group processes. Chapter two discusses an overview of group processes including its history, current social movements, the sequential stages of development, and the school organization. The topic of expectations is treated in chapter three. How expectations develop, teacher expectations and student performance, implications for teachers, and action ideas for change are examined. Leadership and attraction are the topics of chapters four and five respectively. Discussions of Lhe bases of influence, flexible leadership, and classroom liking patterns and their effects on academic performance are included. Chapters six, seven, eight, and nine deal with norms, communication, cohesiveness, and sequential stages of development. The book concludes with a chapter on school organization. (Author/RM)
Availability: Wm. C. Brown Company Publishers, 2460 Kerper Boulevard, Dubuque, Iowa 52001 ($5.95 paper cover).
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Change Strategies; Classroom Communication; Classroom Research; Elementary Secondary Education; Expectation; Group Behavior; Group Dynamics; Inservice Teacher Education; Interaction; Leadership; Norms; Peer Groups; Peer Relationship; Student Behavior; Student Development; Teacher Behavior; Teacher Education; Books